Epidemiology of occult hepatitis B and C in Africa: A systematic review and meta-analysis. Issue 12 (December 2022) - Ondigui, Juliette Laure Ndzie; Kenmoe, Sebastien; Kengne-Ndé, Cyprien; Ebogo-Belobo, Jean Thierry; Takuissu, Guy Roussel; Kenfack-Momo, Raoul; Mbaga, Donatien Serge; Tchatchouang, Serges; Kenfack-Zanguim, Josiane; Fogang, Robertine Lontuo; Menkem, Elisabeth Zeuko'o; Kame-Ngasse, Ginette Irma; et al.
Abstract: Background: Occult hepatitis B (OBI) and C (OCI) infections lead to hepatic crises including cases of liver cirrhosis and even hepatocellular carcinoma (HCC). OBI and OCI also pose a significant problem of their transmissibility. This study aimed to assess the overall prevalence of OBI and OCI in the African continent, a region highly endemic for classical hepatitis B and C viruses. Methods: For this systematic review and meta-analysis, we searched: PubMed, Web of Science, African Journal Online and African Index Medicus for published studies on the prevalence of OBI and OCI in Africa. Study selection and data extraction were performed by at least two independent investigators. Heterogeneity (I²) was assessed using the χ² test on the Cochran Q statistic and H parameters. Sources of heterogeneity were explored by subgroup analyses. This study was registered in PROSPERO, with reference number CRD42021252772. Results: We obtained 157 prevalence data for this meta-analysis, from 134 studies for OBI prevalence; 23 studies on OCI prevalence, and a single study on the OBI case fatality rate. The overall estimate for the prevalence of OBI was 14.8% [95% CI = 12.2–17.7] among 18579 participants. The prevalence of seronegative OBI and seropositive OBI was 7.4% [95% CI = 3.8–11.8] and 20.0% [95% CI = 15.3–25.1] respectively. The overall estimate for the prevalence of OCI was 10.7% [95% CI = 6.6–15.4] among 2865 participants. The pooled prevalence of seronegative OCI was estimated at 10.7% [95%CI = 4.8–18.3] and that of seropositive OCI at 14.4% [95%CI = 5.2–22.1]. In Sub-group analysis, patients with malignancies, chronic hepatitis C, and hemodialysis had a higher OCI prevalence. While those with malignancies, liver disorders, and HIV positive registered highest OBI prevalence. Conclusion: This review shows a high prevalence of OBI and OCI in Africa, with variable prevalence between countries and population groups.